Strategi Pengembangan UMKM Kuliner di Propinsi Jawa Tengah Melalui Pendekatan Analisis SWOT - Nurul Juwariyah; Nurul Rizka Arumsari (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) in the development of culinary MSMEs in Central Java Province. A descriptive qualitative approach was used, with data collection conducted through interviews, observations, and secondary document review. Data analysis was performed using the Miles and Huberman interactive model, which allowed for the systematic processing and interpretation of the gathered data. The findings revealed that the key strengths of culinary MSMEs in Central Java include clear market segmentation, strategic locations, and product innovation. These strengths enable the businesses to reach targeted customers effectively and maintain competitiveness in a dynamic market. However, the main weaknesses identified include limited utilization of digital technology and a lack of managerial development, which hinder their ability to scale and improve operational efficiency. The study also highlighted significant opportunities for growth, such as government support for MSMEs and the rapid development of digital technologies that can enhance marketing and operational processes. Despite these opportunities, the threats facing these businesses include intense competition from both local and global players, as well as a low level of interest in entrepreneurship among the younger generation, which limits the growth potential of new businesses. Based on the SWOT analysis, the study proposes a development strategy matrix that MSMEs and policymakers can use to address weaknesses, capitalize on opportunities, and mitigate threats. This strategy emphasizes the need for digital transformation, investment in managerial skills, and fostering an entrepreneurial culture to ensure the sustainable growth of culinary MSMEs in the region. The findings provide valuable insights for both business owners and policymakers to support the development of the culinary sector in Central Java